Citizen science in plastic composting: a practical approach to the search for PLA-degrading microorganisms - Theodoropoulos, Elisabeth; Kirschke, Sabrina; Walleck, Wiebke; Philipp, Bodo (Frontiers in Environmental Science, 2026)
Citizen science (CS) is becoming increasingly important in exploring the disintegration of plastics in the environment and has positive implications for both science and society. However, it is rarely used in microbiological research and especially in exploring the biodegradation of bioplastics. In this proof-of-concept study, a CS approach is applied to investigate the disintegration of bioplastics in home composts in Germany with the aim of (i) searching for microorganisms with the potential to degrade the bioplastic polylactic acid (PLA) and (ii) exploring attitudes and behavior of the participating citizens in this area and how these may be affected by the citizen science project. Our assumption is that domestic composts are so diverse that bacteria capable of degrading PLA under non-industrial conditions may have (already) evolved in respective composts. Over a period of 3 months, 45 citizens carried out a complex scientific experiment on the degradation of PLA in their household composts, which were distributed throughout Germany. These experiments were accompanied by a pre- and post-survey to analyze the impact of the CS project on the participating citizens. Based on the citizens’ observation that the positive control (paper) was degraded in all cases, we demonstrate that a complex biodegradation experiment performed by citizens is feasible. However, the experiment did not lead to the isolation of PLA-degrading microorganisms. The pre-and post-tests of this short-term intervention on attitudes and behavior hardly reveal any effects in the areas of waste management, consumption and bioplastics.